PENERAPAN BALANCED SCORECARD PADA PD. BPR BANK PASAR KABUPATEN KUDUS - Pujiastuti, Herlina; Nugraha, Hari Susanta; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
A new measurement system based on performance become necessity in managing an organization. The study was conducted in District Company BPR Bank Pasar Region of Kudus. The research design is for performance measurement model business balanced scorecard approach through four perspectives: financial, customer, internal business processes and learning and growth. Performance measurement model is considered able to balance financial performance with non-financial performance.Type of research is a case study. The data used in this study is primary data obtained through focus group discussion (FGD) and using data collection instruments such as questionnaires. And secondary data from the bank's financial statements for 2009, 2010 and 2011. Data analysis begins with translating the vision and mission into strategic goals, set targets and weights through the FGD, performing measurements on each perspective and calculates a score balanced scorecard. Based on the analysis, it could be concluded that the balanced scorecard is a total score of 94.12 and in the category of healthy according to predicate the health of BPR. Financial and customer perspectives in the category of healthy as expected, but in the perspective of internal business processes and learning and growth in the category is quite healthy. Advice can be given to the company is to improve the performance of the non-financial aspects, especially in the perspective of internal business processes and learning and growth.